Influence of sensory stimuli on brand experience, brand equity and purchase intention - Moreira, António C.; Fortes, Nuno; Santiago, Ramiro (Journal of Business Economics and Management, 2017)
Sensory stimulation is used by various brands to induce desired behaviours among their customers. Although its effectiveness is recognised in business contexts, little research has been conducted on sensory marketing. In order to contribute to filling this gap, this study sought to build a model that explains how sensory stimulation influences intentions to purchase a brand. Brand experience and brand equity were expected to mediate this relationship. The empirical validation of the model was conducted by carrying out an online survey with a convenience sample of 302 customers of a brand of the catering industry. The data collected were processed using PLS-SEM methodology. The results reveal that sensory stimulation positively influences brand experience and brand equity, which, in turn, have a positive impact on intentions to purchase the brand in question. The relevant contributions that emerged from this study include not only bridging the aforementioned gap in the literature but also offering significant managerial implications.